Effects of noble metal poisoning on NH_3-SCR performances of Cu-SSZ-13 catalyst - XUE Sen; DING Wenqing; HAN Xuewang; CAO Hehe; ZHANG Yan; YU Yunbo; SHAN Yulong; SHAN Wenpo* (能源环境保护)
Nitrogen oxides (NO_x) from diesel exhaust can induce severe air pollution problems. Selective catalytic reduction of NO_x with NH_3( NH_3-SCR) is the dominant technology for NO_x abatement from diesel vehicles, and Cu-SSZ-13, with excellent NH_3 -SCR activity and hydrothermal stability, has been widely used as the NH_3 -SCR catalyst on diesel vehicles of China VI. In the aftertreatment system of diesel vehicles, Cu-SSZ-13 catalyst can be poisoned by the migration of noble metals from oxidation catalysts, and its NH_3-SCR performance will be affected. In this study, the effects of noble metals with different types and concentrations on the performances of Cu-SSZ-13 catalyst were investigated, and the regeneration effects of hydrothermal aging on noble metal poisoning were also analyzed. When the loading amount of noble metal reached a certain level, the performance of Cu-SSZ-13 was significantly affected, especially the high temperature activity. Hydrothermal aging could restore the NO_x conversion of poisoned catalyst to a certain extent, but the formation of N_2O as a byproduct was promoted. Noble metals of Pt and Pd had similar effects on Cu-SSZ-13. The results of XRD (X-ray diffraction) and N_2 physical adsorption showed that the noble metals had no obvious influence on thestructure of Cu-SSZ-13, but they could slightly reduce the specific surface area and pore volume ofthe catalyst. According to the results of separate NH_3 oxidation and NO oxidation, noble metal poisoning could promote the occurrence of side reactions and induce over consumption of NH_3, thus decreasing the NO_x conversion over Cu-SSZ-13 due to lack of reducing agent. This study is helpful to understand the poisoning effects and mechanism of noble metals on commercial Cu-SSZ-13 catalyst for NH_3-SCR.